Hubungan Penggunaan Kontrasepsi Hormonal Dengan Kejadian Preeklampsia Di RSUP Persahabatan - Junnata, Agung; Marliany, Lily; Pudyastuti, Sri (Jurnal Kedokteran Meditek, 2026)
Introduction: Preeclampsia is one of the leading causes of maternal morbidity and mortality in Indonesia. Several studies have reported that hormonal contraception may affect blood pressure and vascular function, thereby potentially contributing to the development of preeclampsia. However, the available evidence remains inconsistent. Purpose: This study aimed to determine the association between maternal age, parity, and history of contraceptive use, particularly hormonal contraception, and the occurrence of preeclampsia among pregnant women. Methods: This study employed an observational analytic design with a cross-sectional approach using secondary data from the medical records of pregnant women at RSUP Persahabatan Jakarta during May–July 2025. A total of 138 respondents were selected using a simple random sampling technique. Univariate analysis was conducted to describe subject characteristics, while bivariate analysis was performed using the Chi-square test or Fisher’s exact test, with a significance level of (p < 0.05.) Results: The prevalence of preeclampsia was 10.87%. There was a significant association between maternal age and the occurrence of preeclampsia (p < 0.001), as well as between parity and preeclampsia (p = 0.049). A history of contraceptive use was also significantly associated with preeclampsia (p = 0.014). However, no significant association was found between the type of contraception (hormonal vs non-hormonal) or the duration of hormonal contraceptive use and preeclampsia. Conclusion: Maternal age, parity, and history of contraceptive use were associated with preeclampsia. However, the type and duration of hormonal contraceptive use were not shown to increase the risk of preeclampsia in this study population.